Is It Possible Not to Teach Philosophy? A Pocket Roadmap through Theories of History and History Education: A Pocket Roadmap through Theories of History and History Education - Černín, David (Ruch Filozoficzny, 2023)
Knowledge of philosophy is commonly imparted in various philosophy courses, and the teaching process may take multiple forms, ranging from a historical overview to interdisciplinary approaches. However, the theoreticians of education across different subjects and disciplines often turn to philosophy, and they adopt some philosophical assumptions about their field to set up warranted goals and methods of teaching, delineate subject matter, and identify skills they hope to impart. Due to this process involving lengthy theoretical discussions and intellectual exchanges, teachers pass on specific philosophical attitudes even if they are not explicitly teaching philosophy. This paper examines an intersection between history education and philosophy in particular. The focus is on philosophical theories of history that history educators directly address. The paper navigates a specific roadmap portraying the development of the philosophical approaches to the knowledge of the past, discusses diverging traditions, and shows their potential contribution to reaching educational goals.